Protecting mass-gathering events in a pandemic with testing tracks and transparent information: an experimental study with festival guests. - Rebitschek, Felix G.; Eisenmann, Yvonne; Krippner, Lena; Neugebauer, Edmund; Schirren, Clara O.; Schnuppe, Kristin; Hauptmann, Michael (Psychology & Health, 2025)
Objective. To enable future open-air festivals during a pandemic, model festivals tested restricted access and behavioural rules to prevent SARS-CoV-2 transmissions. However, the uptake of health-protective measures depends on informed acceptance, meaning people are more likely to follow measures if they understand their effectiveness and related disease risks. Design and main outcome measures. With a series of online surveys, we studied risk perceptions of 6,500 festival guests and the association of perceived effectiveness of protective behaviours with reported compliance. In a scenario-based online experiment (N = 1,958) among festival guests, we tested the effect of informing transparently about the risk-reducing potential of protective measures at festivals on the intention to attend hypothetical events. Results. We found that guests tended to overestimate infection risks while still perceiving them as low. Self-reported mask wearing and distancing at and around the festivals could not be associated with the understanding of the measures' effectiveness. However, in addition to protective measures themselves, providing transparent information about their absolute risk-reducing effect increased intentions to attend festivals that employ varying protective measures. Conclusion. Our findings suggest that the acceptance of protected festivals can be influenced by transparent information about the effectiveness of protective measures. This calls for further research on evidence-based public health communications to improve their impact.